Integrated Reporting and Protection of Non-Financial Stakeholders in Nigerian Deposit Money Banks - Nwaobia, Appolos N; Ogundajo, Grace O; Abe, Peter O (Journal of Accounting, Business and Finance Research, 2022)
Disclosure quality is the motivation behind every corporate reporting development and, more recently, integrated reporting (IR). However, the concern is its focus and coverage. Studies have shown that IR gives more protection to financial capital providers than to other stakeholders. Thus, this study examines the impact of IR on non-financial stakeholder (employee, customer, and society) protection in Nigeria with a focus on deposit money banks (DMBs). This study sampled and analyzed 13 DMBs listed on the Nigerian Exchange (NGX) as of December 31, 2020. The study found that IR had a significant difference in pre- and post-IR framework eras and a significant effect on employee, customer, and society protection. The study concludes that IR affects the protection of non-financial stakeholders in Nigerian DMBs. It is recommended that regulators, corporate leaders, and researchers should pay more attention to non-financial stakeholders and treat them as capital rather than a way to achieve corporate performance.